Micronutrient dynamics and deficiency risk across pregnancy and postpartum in a Slovak cohort - Alexandra Kristufkova; Neha Basheer; Katarina Koprdova; Matus Lieskovsky; Michal Fresser; Norbert Zilka (PLoS ONE, 2025)
Objective To assess the dynamics in blood concentrations of vitamins (A, B6, B12, D, E,), trace elements such as selenium, magnesium, zinc, and iron (transferrin), and metabolite homocysteine during pregnancy and postpartum. Design Cross-sectional, national cohort study conducted between January and June 2024. Setting Slovakia. Population Pregnant and postpartum women. Methods From venous blood and capillary dry blood spot micronutrients were analysed using standard biochemical and biophysical methods. Main outcome measures Group differences in blood micronutrient levels across pregnancy and postpartum. Results Our findings reveal significant differences in maternal micronutrient levels across pregnancy and postpartum. While some nutrients, including vitamin D and folate, remained relatively stable, others such as vitamin A, B12, iron and zinc were observed at lower levels, and vitamin E at higher levels during pregnancy. Vitamin E levels in the 3rd trimester frequently exceeded reference values for the general adult population, whereas zinc levels were significantly lower postpartum. We observed high prevalence of vitamin B12 and iron deficiencies, as indicated by transferrin saturation, particularly in the 3rd trimester. Vitamin D deficiency was prevalent throughout pregnancy and postpartum. Finally, our analysis demonstrated that dried blood spot (DBS) technology provides comparable results to venous blood analysis for measuring vitamin A, D and homocysteine levels.